The Utilization of Comic as Learning Media to Fulfill Student's Learning Needs - Dian Wicaksono; Wanda Nugroho Yanuarto (Proceedings Series on Social Sciences & Humanities, 2025)
According to national educational report card, SDN Semaya achieved score 63.1 which classified as moderate in terms of learning quality matters. The quality of learning has a root problem in the form of "Program Benahi", a program to improve the quality of learning process. This program recommended increasing the teaching team competencies and policies that support learning process improvement. The Author attempts to implement good practices, by motivating fellow teachers in SDN Semaya to learn contents related to meaningful and student-centered teaching skills. This practice is in line with the revitalization of the Teacher Working Group (KKG) program which is currently being implemented within the Banyumas Regency Office. This program is implemented within the school in form of training using educational comic media to fulfill students’ learning needs. Based on this program, it can be concluded that the use of educational comics to meet learning needs is very necessary. Visual based learning style will increase their attention span through the media visual stimulation. The Digital-based Educational Comics from Canva will give an opportunity to improve the teaching team's competence on delivering learning process.